PENGARUH CUSTOMER SERVICE, INKLUSI KEUANGAN, BUNGA PINJAMAN, DAN TEKNOLOGI TERHADAP MINAT PAYLATER - Setiawan, Doni; Wibowo, Purwo Adi (Media Mahardhika, 2025)
The purpose of this study is to ascertain how customer service affects, financial inclusion, loan interest rates, and technology on the interest of factory employees in Jepara in using PayLater services. The research employs a quantitative approach, with the population being factory workers at PT Kanindo Makmur Jaya Welahan Jepara. The sample consists of 100 respondents aged 20-25 years, chosen by purposive sampling approaches combined with a non-probability sampling approach. Partial Least Squares (PLS) was used for data analysis.The findings indicate that the customer service and loan interest rate variables do not have a positive relationship. However, financial inclusion and technology have a positive effect on employees' interest in using PayLater services.